Process evaluation of the midwifery initiated oral health‐dental service program: Perceptions of dental professionals. (30th December 2018) - Ajwani, Shilpi; Sousa, Mariana S.; Villarosa, Ariana C.; Bhole, Sameer; Johnson, Maree; Dahlen, Hannah G.; Hoolsema, Julia; Blinkhorn, Anthony; Srinivas, Ravi; Yaacoub, Albert; Milat, Andrew; Skinner, John; et al.
Abstract: Issue addressed: All pregnant women should have a comprehensive oral health evaluation. Unfortunately, many pregnant women seldom seek dental care and some dentists are hesitant to treat during pregnancy. To address these issues, the Midwifery Initiated Oral Health Dental Service (MIOH‐DS) program was developed in Australia. The aim of this study was to undertake a process evaluation and explore the perceptions of dental professionals involved in the program to determine the acceptability, feasibility and effectiveness of the program if it were to be upscaled. Methods: A qualitative approach using content analysis was conducted on data from two focus groups involving 12 dental professionals. Results: All participants were supportive of the MIOH‐DS program. They thought pregnant women were receptive to their care, and reported markedly improved oral health. The provision of free dental care and the involvement of midwives were cited as major factors that improved the uptake of the program. Some of the challenges encountered were the prevailing misconceptions about the safety of dental treatment and pregnancy‐related impairments. Conclusions: Dental professionals found the MIOH‐DS to be acceptable, feasible and effective in improving oral health of pregnant women and their uptake of dental services. However, some challenges need to be addressed as the MIOH‐DS program is upscaled into a cost‐effective model. So what?: Dental professionals are important stakeholders in the MIOH‐DS model. The process evaluation of the successful dental intervention is necessary to understand how and why such interventions work, and is an important step in scaling up to a population‐wide intervention.